2013
DOI: 10.1038/nrgastro.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

From NAFLD to NASH to cirrhosis—new insights into disease mechanisms

Abstract: NAFLD has evolved as a serious public health problem in the USA and around the world. In fact, NASH-the most serious form of NAFLD-is predicted to become the leading cause of liver transplantation in the USA by the year 2020. The pathogenesis of NAFLD and NASH, in particular the mechanisms responsible for liver injury and fibrosis, is the result of a complex interplay between host and environmental factors, and is at the centre of intense investigation. In this Review, we focus on recently uncovered aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
430
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(446 citation statements)
references
References 114 publications
8
430
1
7
Order By: Relevance
“…An increase in hepatocyte cell death by apoptosis is typically present in patients with NAFLD and in experimental models of this disease, 31,32 The two fundamental pathways of apoptosis, the extrinsic (death receptor-mediated) and intrinsic (organelleinitiated) pathways, are involved. 31 The results of the current study demonstrate that selective deletion of Bid in hepatocytes protects from DEN-induced tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in hepatocyte cell death by apoptosis is typically present in patients with NAFLD and in experimental models of this disease, 31,32 The two fundamental pathways of apoptosis, the extrinsic (death receptor-mediated) and intrinsic (organelleinitiated) pathways, are involved. 31 The results of the current study demonstrate that selective deletion of Bid in hepatocytes protects from DEN-induced tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in hepatocyte cell death by apoptosis is typically present in patients with NAFLD and in experimental models of this disease, 31,32 The two fundamental pathways of apoptosis, the extrinsic (death receptor-mediated) and intrinsic (organelleinitiated) pathways, are involved. 31 The results of the current study demonstrate that selective deletion of Bid in hepatocytes protects from DEN-induced tumorigenesis. Due to the fact that the initial cellular damage occurring within the first days of DEN injection is known to be of major importance in HCC induction, 7 we assessed the livers of mice 48 h after DEN injection and observed that Bid Δhep mouse livers were protected from the hepatocyte cell death, compensatory proliferation and inflammatory changes that typically result from DEN administration.…”
Section: Discussionmentioning
confidence: 99%
“…As with GSC and GDD the difference between the two is based on the interplay of host genetics and immunology, to the presence of fat in the liver. NASH is associated with defined genes, which is not associated with NAFLD [48,49].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The prevalence of NAFLD is estimated to range from 25 to 37% of the general population (1)(2)(3)(4), and it constitutes a common etiological factor of chronic liver disease worldwide. Non-alcoholic steatohepatitis (NASH) is a progressive form of NAFLD.…”
Section: Introductionmentioning
confidence: 99%